PEMBERDAYAAN PETERNAK MELALUI PELATIHAN PEMBUATAN PUPUK KOMPOS DESA SOROPIA KECAMATAN SOROPIA KABUPATEN KONAWE - Pagala, Muhammad Amrullah; Nafiu, La Ode; Rahman, Rahman; Malesi, La; Libriani, Restu; Munadi, La Ode Muh; Badaruddin, Rusli (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Community service activities integrated with KKN-THEMATIC carried out by the UHO Faculty of Animal Husbandry Lecturer Team took place in Soropia Village, Soropia District, Konawe Regency. Compost is an organic fertilizer produced through the process of decomposition of organic materials, especially animal waste, by active microorganisms such as bacteria and fungi. The purpose of this service is to provide training and technology transfer in making compost. The methods used include delivering materials and demonstrations. In this activity, training in making compost was carried out by utilizing cow dung which is widely available around the Soropia Village settlement, which is then mixed with super decomposer EM4, rice husks, granulated sugar, and water. Through this training, the community is given knowledge about the use of waste from agriculture and livestock to be processed into useful products, especially in the fields of livestock and organic farming which are currently developing in Soropia Village. The farmers showed high enthusiasm during this activity and appreciated the service carried out, with the hope that similar activities can be continued in the future.